2012
DOI: 10.20450/mjcce.2012.58
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the seed and seed extracts of the pumpkins Cucurbita maxima D. and Cucurbita pepo l. from Macedonia

Abstract: Chemical composition of seeds of C. maxima D. and C. pepo L. cultivated in the Republic of Macedonia and physico-chemical characteristics, fatty acid profiles, and sterol and tocopherol contents in pumpkin seed extracts were determined. Higher kernel yield and content of moisture, ash, total nitrogen, proteins and carbohydrates were measured in the C. pepo than in C. maxima seed. The highest extract yield of 487.4 g/kg dry matter was obtained from C. pepo kernel, while 388.2 g/kg dry matter was extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 24 publications
9
13
1
Order By: Relevance
“…The saponification values of the oils were increasing with respect to the increasing polarities of the solvents signifying the influence of the solvent polarity on oil quality. The saponification values obtained in this study are in agreement with what other authors previously reported on pumpkin spp seed oil extracted using nhexane by shaking and in soxhlet apparatus (Ardabili et al, 2011;Srbinoska et al, 2012). However, Chatepa and Masamba 45 saponification values for acetone and ethanol extracted oils were more than 91.16±3.63 mg KOH/kg for pumpkin (Telfairia occidentalis) seeds oil extracted using petroleum ether in a soxhlet apparatus (Eddy et al, 2011) and 44.88 mg KOH/kg (Eze, 2012) using n-hexane in a soxhlet apparatus reported in Nigeria.…”
Section: Effect Of Solvent Type and Polarity On Saponification Valuesupporting
confidence: 93%
See 4 more Smart Citations
“…The saponification values of the oils were increasing with respect to the increasing polarities of the solvents signifying the influence of the solvent polarity on oil quality. The saponification values obtained in this study are in agreement with what other authors previously reported on pumpkin spp seed oil extracted using nhexane by shaking and in soxhlet apparatus (Ardabili et al, 2011;Srbinoska et al, 2012). However, Chatepa and Masamba 45 saponification values for acetone and ethanol extracted oils were more than 91.16±3.63 mg KOH/kg for pumpkin (Telfairia occidentalis) seeds oil extracted using petroleum ether in a soxhlet apparatus (Eddy et al, 2011) and 44.88 mg KOH/kg (Eze, 2012) using n-hexane in a soxhlet apparatus reported in Nigeria.…”
Section: Effect Of Solvent Type and Polarity On Saponification Valuesupporting
confidence: 93%
“…The findings in this study have shown that the choice of solvents, with respect to solvent polarity, influences the oil quality in terms of acid value. The acid value of oil extracted using cyclohexane was similar to 2.05 for Cucurbita mixta oil (Borhade, 2012) but lower compared to values of 4.07 and 4.71 mg KOH/g reported by other authors (Srbinoska et al, 2012) for C. maxima and Cucurbita pepo seed oil extracted using n-hexane in soxhlet apparatus. The Codex Alimentarius Commission (1982) recommended the maximum acid value of 10 and 4 mg KOH/g oil for virgin palm and coconut oil respectively.…”
Section: Effect Of Solvent Type and Polarity On Acid Valuesupporting
confidence: 70%
See 3 more Smart Citations